Analisis Perhitungan Pajak Pertambahn Nilai (PPN) Pembelian Dan Penjualan Barang Sebelum Dan Sesudah Pandemi Pada Pt.Seah Precision Metal Indonesia Tahun 2019-2022 - Mislam Mislam; Siti Nuridah; Siti Ayu Rosida (Journal Economic Excellence Ibnu Sina, 2023)
This research basically discusses the analysis of the calculation of input tax and output tax in order to determine the underpayment or overpayment of VAT at PT Seah Precision Metal Indonesia in 2019-2022. In calculating Value Added Tax (VAT), it is one of the tax obligations that must be carried out by the company PT. Seah Precision Metal Indonesia, which is a corporate tax that has been carried out as a taxable entrepreneur at the tax services office.The population in this research is the company PT. Seah Precision Metal Indonesia using the 2019-2022 Input VAT and Output VAT reporting period. The research method used in this research is a qualitative method with data analysis using Excel. The results of this research show that none of the manufacturing companies PT. Seah Precision Metal Indonesia in 2019-2022 have overpaid tax status. All samples in this study had underpaid tax status. And there were sales and purchases before the pandemic, during the pandemic, and after the pandemic in 2019-2022, the difference between sales and purchases of goods was the lowest in 2021, compared to 2019.